Pregnancy in a Woman with Homozygous Familial Hypercholesterolemia Not on Low-Density Lipoprotein Apheresis - Fahed, Akl C.; Nassar, Anwar H. (American Journal of Perinatology Reports, 2012)
Pregnancy in women with homozygous familial hypercholesterolemia (FH) has been rarely reported and might pose risks on the mother and her fetus. Although most reported cases remained on low-density lipoprotein (LDL) apheresis, there are no clear guidelines regarding the management of this entity. We report the first case of an uncomplicated pregnancy in a 24-year-old homozygous FH woman who was not maintained on LDL apheresis. FH expresses a wide variability in the phenotype, and management of homozygous FH cases who desire to become pregnant should be individualized based on preconceptional assessment with frequent antenatal follow-up. Decisions on management should be made after weighing the risks versus benefits of LDL apheresis.
Keywords: homozygous familial hypercholesterolemia; pregnancy; LDL apheresis; outcome